Strategi Pengembangan Sistem Insentif yang Berkeadilan bagi Tenaga Penjualan dalam Meningkatkan Daya Saing Organisasi - Rini Falensia; Medy Idrian Witrisna; Arisandi Arisandi; Sentot Imam Wahjono (MAN 4 Kota Pekanbaru, 2025)
This study addresses the low effectiveness of human resource (HR) strategies, which affects employee performance and organizational outcomes. The purpose is to examine the effectiveness of a fair incentive system for sales personnel and strategies for its development to enhance organizational competitiveness. Using a library research method, secondary data were collected from scientific journals (2020-2025) via the Publish or Perish application. Data were analyzed qualitatively and descriptively through content analysis, comparing perspectives from various studies to identify similarities, differences, and research gaps. Findings indicate that a fair incentive system enhances motivation, productivity, and loyalty when it applies principles of fairness in distribution, procedures, and interactions. Effective incentive strategies integrate financial and non-financial rewards, leverage innovation and digital tools, and promote two-way communication. Combining individual and group incentives fosters team synergy and strengthens organizational competitiveness. The study highlights that transparent and performance-relevant incentives are essential for sustainable HR development and organizational success.